Internalization of Entrepreneurship Education in Tourism Awareness Groups: Evidence from Indonesia - Djoko Dwi Kusumojanto; Indrayani Indrayani; Novia Tri Hapsari (Faculty of Economics, State University of Jakarta., 2021)
The inadequacy of entrepreneurship in Indonesia is becoming an interesting problem to study, and therefore the solution will be obtained through entrepreneurial education. Higher education plays an essential role in creating sustainable entrepreneurs. Therefore, this study aims to determine the internalization of entrepreneurship education in increasing the skills and knowledge in the Mentawir Mangrove Tourism Village community. This research uses a qualitative approach, with a type of phenomenology. Researchers act as implementers, observers, data collectors, data analyzers, giving actions, and at the same time producing research reports. In-depth interviews and observations with informants carried out data collection in this study. Data analysis in this study is using an interactive model. The results showed that the internalization of entrepreneurship education in the Mentawir Mangrove Tourism Village community is carried out traditionally. However, the output of the entrepreneurial education internalization process begins with creativity by the Tambun Tiram Tourism Awareness group in the form of mangrove syrup and bamboo handicraft production activities.